Differences in Student Career Orientation Come From The Banjar and Javanese Tribes - Solihin, Muhammad Hayatus; Sulistiyana, Sulistiyana; Sugianto, Akhmad (Universitas Muhammadiyah Metro, 2023)
Choosing a career is not an easy thing for a teenager to go through. Several factors, including the influence of the family environment and culture, influence a person's career orientation. Cultural differences between ethnic groups can result in a different orientation to individual careers. This study uses a quantitative approach with a comparative type and a sampling technique using purposive sampling with a questionnaire data source. Based on the survey results from various aspects, it can be seen that students from the Banjar and Javanese tribes are superior in career planning to the other three factors. The information aspect of the world of work is the element with the lowest score, and there is little difference between Banjarese students and Javanese students. From this study, it can be concluded that there is no significant difference between the average career orientation of students in the Banjar and Javanese.